Atmospheric assessment of polychlorinated naphthalenes (PCNs) and polychlorinated biphenyls (PCBs) using pine needles in Detroit, Michigan - Sung-Hee Seo; Tian Xia; Adriana C. Torres-Moreno; Md Kamrul Islam; Stuart Batterman (Journal of Hazardous Materials, 2026)

Estimation of vehicle PM2.5 emissions with high spatio-temporal resolution and its application to air dispersion modeling in Seoul, South Korea - Sang-Jin Lee; Stuart Batterman (Environmental Pollution, 2026)

Reduced-form air quality dispersion modeling for urban scale traffic-related pollutants - Sang-Jin Lee; Stuart Batterman (Science of The Total Environment, 2025)

Development and performance evaluation of an analytical method for the analysis of polychlorinated naphthalenes (PCNs) and polychlorinated biphenyls (PCBs) accumulated in pine needles - Sung-Hee Seo; Adriana C. Torres-Moreno; Stuart Batterman (Chemosphere, 2025)

Polychlorinated naphthalenes (PCNs) and polychlorinated biphenyls (PCBs) in surface soils and street dusts in Detroit, Michigan - Sung-Hee Seo; Tian Xia; Md Kamrul Islam; Stuart Batterman (Science of The Total Environment, 2025)

Associations of serum persistent organic pollutant concentrations with incident diabetes in midlife women: The Study of Women’s Health Across the Nation Multi-Pollutant Study - Amelia Grant-Alfieri; William H. Herman; Deborah J. Watkins; Stuart Batterman; Carrie Karvonen-Gutierrez; Sung Kyun Park (Environmental Research, 2024)

Development and performance of an analytical method for polychlorinated naphthalenes and other persistent organic pollutants in dried blood spots - Sung-Hee Seo; Stuart Batterman (Analytica Chimica Acta, 2024)

Modeling airborne pollen concentrations at an urban scale with pollen release from individual trees - Daniel S. W. Katz; Alan P. Baptist; Stuart A. Batterman (Aerobiologia, 2023)

Association between toxic and essential metals in blood and global DNA methylation among electronic waste workers in Agbogbloshie, Ghana - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Duah Dwomoh; Thomas P. Agyekum; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (Environmental Science and Pollution Research, 2022)

Associations of self-reported occupational exposures and settings to ALS: a case–control study - Stephen A. Goutman; Jonathan Boss; Christopher Godwin; Bhramar Mukherjee; Eva L. Feldman; Stuart A. Batterman (International Archives of Occupational and Environmental Health, 2022)
Background Environmental exposures contribute to the pathogenesis of amyotrophic lateral sclerosis (ALS), a fatal and progressive neurological disease. Identification of these exposures is important for targeted screening and risk factor modification. Objective To identify occupational exposures that are associated with a higher risk of ALS using both survey and standard occupational classification (SOC) coding procedures, and to highlight how exposure surveys can complement SOC coding. Methods ALS participants and neurologically healthy controls recruited in Michigan completed a detailed exposure assessment on their four most recent and longest held occupations. Exposure scores were generated from the exposure survey, and occupations were assigned to SOC codes by experienced exposure scientists. Results This study included 381 ALS and 272 control participants. ALS participants reported higher duration-adjusted occupational exposure to particulate matter (OR = 1.45, 95% CI 1.19–1.78, p < 0.001), volatile organic compounds (OR = 1.22, 95% CI 1.02–1.45, p = 0.029), metals (OR = 1.48, 95% CI 1.21–1.82, p < 0.001), and combustion and diesel exhaust pollutants (OR = 1.20, 95% CI 1.01–1.43, p = 0.041) prior to ALS diagnosis, when adjusted for sex, age, and military service compared to controls. In multivariable models, only occupational exposure to metals remained significant risk (OR = 1.56, 95% CI 1.11–2.20, p = 0.011), although in an adaptive elastic net model, particulate matter (OR = 1.203), pesticides (OR = 1.015), and metals (1.334) were all selected as risk factors. Work in SOC code “Production Occupations” was associated with a higher ALS risk. SOC codes “Building and Grounds Cleaning and Maintenance Occupations”, “Construction and Extraction Occupations”, “Installation, Maintenance, and Repair Occupations”, and “Production Occupations” were all associated with a higher exposure to metals as determined using survey data. Discussion Occupational exposure to particulate matter, volatile organic compounds, metals, pesticides, and combustion and diesel exhaust and employment in “Production Occupations” was associated with an increased ALS risk in this cohort.

Global DNA (LINE-1) methylation is associated with lead exposure and certain job tasks performed by electronic waste workers - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Thomas P. Agyekum; Duah Dwomoh; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (International Archives of Occupational and Environmental Health, 2021)

Development of a mobile platform for monitoring gaseous, particulate, and greenhouse gas (GHG) pollutants - Tian Xia; James Catalan; Chris Hu; Stuart Batterman (Environmental Monitoring and Assessment, 2021)

Urban-scale variation in pollen concentrations: a single station is insufficient to characterize daily exposure - Daniel S. W. Katz; Stuart A. Batterman (Aerobiologia, 2020)

Pollen production for 13 urban North American tree species: allometric equations for tree trunk diameter and crown area - Daniel S. W. Katz; Jonathan R. Morris; Stuart A. Batterman (Aerobiologia, 2020)

Absence of PCB Hot Spot Effect in Walleye Sander vitreus from Lower Green Bay of Lake Michigan - Charles P. Madenjian; Daniel J. Dembkowski; Daniel A. Isermann; Stuart A. Batterman; Sergei M. Chernyak; Stewart F. Cogswell; Mark E. Holey (Archives of Environmental Contamination and Toxicology, 2019)

VOC sources and exposures in nail salons: a pilot study in Michigan, USA - Lexuan Zhong; Stuart Batterman; Chad W. Milando (International Archives of Occupational and Environmental Health, 2019)

Air pollutant strategies to reduce adverse health impacts and health inequalities: a quantitative assessment for Detroit, Michigan - Sheena E. Martenies; Chad W. Milando; Stuart A. Batterman (Air Quality, Atmosphere & Health, 2018)

Use of free-standing filters in an asthma intervention study - Stuart Batterman; Liuliu Du; Edith Parker; Thomas Robins; Toby Lewis; Bhramar Mukherjee; Erminia Ramirez; Zachary Rowe; Wilma Brakefield-Caldwell (Air Quality, Atmosphere & Health, 2013)

Composition and Integrity of PAHs, Nitro-PAHs, Hopanes, and Steranes in Diesel Exhaust Particulate Matter - Lei Huang; Stanislav V. Bohac; Sergei M. Chernyak; Stuart A. Batterman (Water, Air, & Soil Pollution, 2013)

Evaluating the environmental performance of passenger vehicles - Stuart A. Batterman; William O. Mattick; Lawrence I. Ranka (The International Journal of Life Cycle Assessment, 2001)

Breath, urine, and blood measurements as biological exposure indices of short-term inhalation exposure to methanol - Stuart A. Batterman; Alfred Franzblau; James B. D'Arcy; Nicholas E. Sargent; Kenneth B. Gross; Richard M. Schreck (International Archives of Occupational and Environmental Health, 1998)

Environmental Reporting by the Fortune 50 Firms - Paige Davis-Walling; Stuart A. Batterman (Environmental Management, 1997)